2021
DOI: 10.1093/ibd/izaa354
|View full text |Cite
|
Sign up to set email alerts
|

LRRC19 Promotes Permeability of the Gut Epithelial Barrier Through Degrading PKC-ζ and PKCι/λ to Reduce Expression of ZO1, ZO3, and Occludin

Abstract: Background A dysfunctional gut epithelial barrier allows the augmented permeation of endotoxins, luminal antigens, and bacteria into the bloodstream, causing disease. The maintenance of gut epithelial barrier integrity may be regulated by multiple factors. Herein we analyze the role of leucine-rich repeat-containing protein 19 (LRRC19) in regulating the permeability of the gut epithelial barrier. Methods We utilized Lrrc19 kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…63 TJs play a key role in maintaining the integrity of the intestinal epithelial barrier, with occludin and ZO-1 being crucial proteins associated with intestinal permeability and the mucosal barrier function. 64,65 Importantly, we demonstrated that dietary NOB effectively ameliorated CFX- and LVX-associated intestinal barrier injury by significantly upregulating ZO-1 expression. These results were consistent with previous studies, which showed that NOB enhanced the intestinal barrier function by upregulating occludin and ZO-1 expressions in models of intestinal inflammation.…”
Section: Discussionmentioning
confidence: 80%
“…63 TJs play a key role in maintaining the integrity of the intestinal epithelial barrier, with occludin and ZO-1 being crucial proteins associated with intestinal permeability and the mucosal barrier function. 64,65 Importantly, we demonstrated that dietary NOB effectively ameliorated CFX- and LVX-associated intestinal barrier injury by significantly upregulating ZO-1 expression. These results were consistent with previous studies, which showed that NOB enhanced the intestinal barrier function by upregulating occludin and ZO-1 expressions in models of intestinal inflammation.…”
Section: Discussionmentioning
confidence: 80%
“…Dysfunction in this barrier is a pivotal factor contributing to increased intestinal mucosal permeability, thereby mediating the onset and progression of ulcerative colitis [21] . Two tight junctions composed of ZO and Occludin proteins [22][23][24] form the basis of the integrity of tight junctions. Occludin has the functions of sealing cell space, regulating paracellular transport and regulating signal conduction [25] , etc., while ZO-1 affects cell proliferation, differentiation and growth, and regulates intercellular signal transduction and penetration [26] .…”
Section: Discussionmentioning
confidence: 99%
“…e latest research demonstrated that LRRC19 can increase the permeability of the gut epithelial barrier by degrading PKC to reduce the expression of ZO-1, ZO-3, and occludin [35].…”
Section: Discussionmentioning
confidence: 99%
“…LRRC19 was also mentioned for its therapeutic potential in pressure ulcers, by promoting NF-kB-dependent pro-inflammatory response [ 34 ]. The latest research demonstrated that LRRC19 can increase the permeability of the gut epithelial barrier by degrading PKC to reduce the expression of ZO-1, ZO-3, and occludin [ 35 ].…”
Section: Discussionmentioning
confidence: 99%